K-Pop dan Tiktok: Video Konten SWN Brass Band Sebagai Wujud Kreativitas Bermusik Di Era Pandemi Covid-19 - Puput Meinis Narselina (Universitas Negeri Medan, 2025)
The Tiktok application is a social networking platform that is a medium of expression for millennials to create short videos in line with innovation and changes in technological systems in the era of disruption. As a consequence, users of this application become dependent, especially on fans of K-Pop or popular music originating from South Korea. Tiktok encourages interested K-Pop fans to be as creative as possible with short videos and music. In line with this phenomenon, this research highlights K-Pop music on the Tiktok application which has gone viral in the last few months. The study focuses on YouTube content by the SWN Brass Band into the concept of the Tiktok Medley performance along with video clips. The aim of this research is to descriptively describe K-Pop songs that are currently viral on the Tiktok application by SWN Brass Band as a form of musical creativity. The theory used in this research is the analysis music theory by Leon Stein. This research uses qualitative methods with a musicological approach. Data collection was carried out through interviews who were considered key sources. It is hoped that this research can make a contribution to the Music Study Program, especially related to musical creativity during the pandemic, namely in the massive use and utilization of technological systems.